Genetic and Epigenetic Changes Are Rapid Responses of the Genome to the Newly Synthesized Autotetraploid Carassius auratus - Wang, Chongqing; Zhou, Yuwei; Qin, Huan; Zhao, Chun; Yang, Li; Yu, Tingting; Zhang, Yuxin; Xu, Tao; Qin, Qinbo; Liu, Shaojun (Frontiers in Genetics, 2021)
Whole genome duplication events have occurred frequently during the course of vertebrate evolution. To better understand the influence of polyploidization on the fish genome, we herein used the autotetraploid Carassius auratus (4n = 200, RRRR) (4nRR) resulting from the whole genome duplication of Carassius auratus (2n = 100, RR) (RCC) to explore the genomic and epigenetic alterations after polyploidization. We subsequently performed analyses of full-length transcriptome dataset, amplified fragment length polymorphism (AFLP) and methylation sensitive amplification polymorphism (MSAP) on 4nRR and RCC. By matching the results of 4nRR and RCC isoforms with reference genome in full-length transcriptome dataset, 649 and 1,971 novel genes were found in the RCC and 4nRR full-length geneset, respectively. Compared to Carassius auratus and Megalobrama amblycephala, 4nRR presented 3,661 unexpressed genes and 2,743 expressed genes. Furthermore, GO enrichment analysis of expressed genes in 4nRR revealed that they were enriched in meiosis I, whereas KEGG enrichment analysis displayed that they were mainly enriched in proteasome. Using AFLP analysis, we noted that 32.61% of RCC fragments had disappeared, while 32.79% of new bands were uncovered in 4nRR. Concerning DNA methylation, 4nRR exhibited a lower level of global DNA methylation than RCC. Additionally, 60.31% of methylation patterns in 4nRR were altered compared to RCC. These observations indicated that transcriptome alterations, genomic changes and regulation of DNA methylation levels and patterns had occurred in the newly established autotetraploid genomes, suggesting that genetic and epigenetic alterations were influenced by autotetraploidization. In summary, this study provides valuable novel insights into vertebrate genome evolution and generates relevant information for fish breeding.